Using Infographics In Teaching The Django Web Framework - Kamalova Nilufar Ilkhomovna (Zien Journals, 2024)
The article is devoted to the study of the potential of infographics as an effective learning tool for the Django web framework. It analyzes the relevance of the use of infographics in IT education, examines the advantages of visual representation of complex Django concepts, and describes the principles of creating infographic materials for educational purposes. The article concludes that infographics are an effective tool for better assimilation of material and increasing motivation to study the Django web framework. The article also offers practical recommendations for creating infographics for teaching web development
Keywords: infographics; Django; web framework; IT education